1994
DOI: 10.21273/jashs.119.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone and Storage Temperature on Postharvest Diseases and Physiology of Carrots (Daucus carota L.)

Abstract: Effects of ozone and storage temperature on carrots and two postharvest pathogens—Botrytis cinerea Pers. and Sclerotinia sclerotiorum de Bary—were investigated. Pathogen-inoculated and uninoculated whole carrots were exposed to an ozone concentration of 0 (control), 7.5, 15, 30, or 60 μl·liter-1. Treatment chambers were flushed with a total flow rate of 0.5 liters·min-1 (air and ozone) for 8 h daily for 28 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 19 publications
(20 reference statements)
2
75
2
2
Order By: Relevance
“…Ozone gas concentration, RH and time were all significant factors for the inactivation of E. coli O157: H7 (Liew & Prange, 1997), of which ozone gas concentration was the most important. Moreover, it must be a synergism between ozone gas concentration and RH, while temperature (Manousaridis et al, 2005) may be another important factor for ozone gas effectiveness.…”
Section: Discussionmentioning
confidence: 98%
“…Ozone gas concentration, RH and time were all significant factors for the inactivation of E. coli O157: H7 (Liew & Prange, 1997), of which ozone gas concentration was the most important. Moreover, it must be a synergism between ozone gas concentration and RH, while temperature (Manousaridis et al, 2005) may be another important factor for ozone gas effectiveness.…”
Section: Discussionmentioning
confidence: 98%
“…Interest in the use of ozone increased significantly after it was deemed safe in the USA (Graham 1997) and approved as a recognised food additive by the US-FDA (Karaca and Velioglu 2007). Several studies have shown that ozone can be effectively used to curb food spoilage organisms (Liew and Prange 1994;Barth et al 1995;Sarig et al 1996;Tzortzakis et al 2007aTzortzakis et al , b, 2008, but the specific effects of ozone on the development of such organisms need to be studied if ozone is to be used more effectively. In particular, the impact of different levels of ozone on macroscopic development and micromorphological characters need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, although the results of the analysis of variance indicates a significant change in color hue due to the interaction between ozone concentration and exposure time, the regression coefficients were not significant (p > 0.05). It is noteworthy that the color is an important indicator of product quality and also has influence on consumer perceptions (Carvalho, Chagas, & Souza, 1997) being used to assess the quality of ozonated food (Liew & Prange, 1994;Nadas, Olmo, & García, 2003;Sung, Song, Kim, Ryu, & Kang, 2014). Alencar et al (2011) observed significant variation in color difference of peanut kernels as a function of ozonation.…”
Section: Effect Of Ozonation On Physical and Chemical Quality Variablmentioning
confidence: 99%